Regulating assisted reproduction: Discrimination and the right to privacy. (June 2019) - Shaw, Joshua
Advances in fertility medicine have led some ethicists to call for stricter regulations on assisted reproduction. One counterargument is that such restrictions are unfair, for they impose far more stringent limits on the procreative liberties of individuals who rely on assisted reproductive technology than on those who reproduce through unassisted coital reproduction. This paper argues that a morally relevant distinction can be drawn between these two cases—one that supports stricter regulations on assisted reproduction. The argument, roughly, is this: it is not possible to regulate unassisted reproduction more stringently without violating the right to privacy. However, it is possible to regulate assisted reproduction without violating it, and the moral benefits of doing so warrant stricter regulations. Two arguments are made for this claim. First, it is not possible to regulate procreative rights in cases of unassisted reproduction in isolation from other freedoms—freedoms protected by the right to privacy. However, it is possible to regulate procreative liberties in isolation from other rights in cases of assisted reproduction. Second, procreative rights do not appear in general to be positive rights that entitle their possessors to assistance from others, and hence they are not violated by sterner regulations on assisted reproduction. However, parallel regulations on unassisted reproduction would violate a right to noninterference that is almost certainly protected by the right to privacy.